2015
DOI: 10.1371/journal.pone.0135640
|View full text |Cite
|
Sign up to set email alerts
|

Bocavirus Infection in Otherwise Healthy Children with Respiratory Disease

Abstract: To evaluate the role of human bocavirus (hBoV) as a causative agent of respiratory disease, the importance of the viral load in respiratory disease type and severity and the pathogenicity of the different hBoV species, we studied all hBoV-positive nasopharyngeal samples collected from children who attended an emergency room for a respiratory tract infection during three winters (2009–2010, 2011–2012, and 2013–2014). Human bocavirus was detected using the respiratory virus panel fast assay and real-time PCR. Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
29
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(36 citation statements)
references
References 44 publications
7
29
0
Order By: Relevance
“…Because HBoV infection is very common and frequently found in asymptomatic participants, the pathogenic role of this virus has been questioned [31,32]. Children with higher viral loads tend to have more severe infections [33], longer hospitalization duration [34,35], and are found to have co-infection by other viruses [36,37] less frequently than those with lower viral loads. However, in children in daycare, viral load had no apparent association with severity of illness [31], which also might reflect challenges in reproducibly measuring viral load in secretions.…”
Section: Discussionmentioning
confidence: 99%
“…Because HBoV infection is very common and frequently found in asymptomatic participants, the pathogenic role of this virus has been questioned [31,32]. Children with higher viral loads tend to have more severe infections [33], longer hospitalization duration [34,35], and are found to have co-infection by other viruses [36,37] less frequently than those with lower viral loads. However, in children in daycare, viral load had no apparent association with severity of illness [31], which also might reflect challenges in reproducibly measuring viral load in secretions.…”
Section: Discussionmentioning
confidence: 99%
“…However, few data are available from some clinical studies, where low percentages of positivity for HBoV were found in different types of clinical specimens. Principi and coworkers detected HBoV in 104 (5.7 %) nasopharyngeal samples collected from children attending an emergency room for a respiratory tract infection, all belonging to species 1 (Principi et al 2015). In a study on the prevalence of viral infections in children with community-acquired pneumonia, HBoV was detected in 10 % of samples, mainly in association with other viruses (particularly Respiratory Syncytial virus and rhinovirus) (Mameli and Zuccotti 2013).…”
Section: Discussionmentioning
confidence: 99%
“…RV infections are reported to be most common after 9–12 months of age (30), which is consistent with our findings. The second most common virus was HBoV, a recently discovered pathogen that is detected in 5.7% – 20% of hospitalized children with respiratory illnesses and episodes of wheezing (24, 31). The third most common pathogen during the one-year follow-up was RSV, which was detected in 2% – 15% of children with mean age 12 months at the study entry.…”
Section: Discussionmentioning
confidence: 99%